IMPORTANCE OF VOCABULARY IN ENGLISH FOR SPECIFIC PURPOSES (ESP) TEACHING AND LEARNING - F.S.Makhmudova; S.X.Mashrapova (TADQIQOTLAR.UZ, 2024)
Vocabulary plays a major role in any language acquisition. Language acquisition is commonly seen as an endless process. Having an adequate English vocabulary is essential for ESL and EFL learners, as well as those aiming to learn English for Special Purposes (ESP). This article gives information different types and categorizations of vocabulary as means to raise awareness of the significant role of vocabulary in ESP teaching. It also explores which types of vocabulary to teach and how the ESP teacher can facilitate a given topic in the learning process. The paper concludes by providing suggestions and specific considerations for how to work with vocabulary in EFL and ESP contexts.